2022
DOI: 10.3390/nu15010001
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Human and Animal Evidence on the Role of Buckwheat Consumption on Gastrointestinal Health

Abstract: Background: Buckwheat is a commonly cultivated crop with growing evidence that it is beneficial to gastrointestinal (GI) health. This systematic review summarizes the role of buckwheat in modifying GI health outcomes and microbiomes. Methods: Four medical databases and Google Scholar were systematically searched. Clinical trials, observational studies, animal in vivo, and in vitro studies with human and animal GI-derived samples were included. Results: There were 32 studies (one randomized controlled trial [RC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The microbiota in the colon enable this process [42]. Small-sized phenolic molecules, which result from the colon's microbial conversion, are more easily absorbed than large-sized phenolic metabolites [43][44][45].…”
Section: Bioactivity Of Flavonoids Rutin and Quercetinmentioning
confidence: 99%
“…The microbiota in the colon enable this process [42]. Small-sized phenolic molecules, which result from the colon's microbial conversion, are more easily absorbed than large-sized phenolic metabolites [43][44][45].…”
Section: Bioactivity Of Flavonoids Rutin and Quercetinmentioning
confidence: 99%
“…Recent studies have indicated differences in microbiome composition between adults with SCI or with multiple sclerosis vs those without CNS injuries 6 8 . This imbalance is exacerbated by frequent antibiotic use, physical inactivity, and psychological stress, which collectively disrupt the gut microbiome and promote the growth of inflammation-associated organisms 4 , 9 .…”
Section: Introductionmentioning
confidence: 99%